A forest of time : - Nabokov, Peter (Cambridge University Press, 2002)
A Forest of Time is a superbly written and essential corrective to that great sea of bad history and bad faith generated about 'Indians' since colonial times. Peter Nabokov writes with brilliance, insight, eloquence, precision, and tact. The result is an extraordinary book, one I wish every reader in America would take to heart